Adsorption Of 4-Nitrophenol And 4-Chlorophenol Onto Biomass-based activated Carbon kinetic and Equilibrium Studies. - Chin, Lip Han (2006)
The adsorption studies of 4-nitrophenol and 4-chlorophenol from aqueous solution on activated carbon previously prepared in laboratory from rattan saw dust by physiochemical process at 850°C have been studied.